2022
DOI: 10.3389/fimmu.2022.844401
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Microbiota and Pancreatic Cancer: Opportunities and Limitations

Abstract: The human body is thoroughly colonized by a wide variety of microorganisms, termed microbiota. Pancreatic cancer, one of the most aggressive forms of cancer, is no exception. The microbiota of pancreatic cancer largely influences and even dominates the occurrence, development and outcome of pancreatic cancer in many ways. Studies have shown that microbiota could change the malignant phenotype and prognosis of pancreatic cancer by stimulating persistent inflammation, regulating the antitumor immune system, chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 149 publications
0
22
0
Order By: Relevance
“…Despite substantial advances in understanding the importance of microbiota for human health, the potential impact of the microbiota on tumor growth, progression, and treatment response remained unclear until recently. Additionally, the fact that microbiota populations are large and symbiotic within the human body, influenced by factors like age, sex, immune competence, diet, climate, geography, and various other aspects, complicates the use of microbiota for precision therapy 143,531 . A thought‐provoking question is whether certain probiotics yield beneficial effects on the organism in specific environments, such as the gut, and whether their colonization in other tissues also offers benefits—this needs careful assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite substantial advances in understanding the importance of microbiota for human health, the potential impact of the microbiota on tumor growth, progression, and treatment response remained unclear until recently. Additionally, the fact that microbiota populations are large and symbiotic within the human body, influenced by factors like age, sex, immune competence, diet, climate, geography, and various other aspects, complicates the use of microbiota for precision therapy 143,531 . A thought‐provoking question is whether certain probiotics yield beneficial effects on the organism in specific environments, such as the gut, and whether their colonization in other tissues also offers benefits—this needs careful assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Microbiota can alter the malignant phenotype of tumors by inducing inflammation, modulating the antitumor immune system, altering TME, and influencing cellular metabolism, and is strongly linked to tumor patients' prognosis 143,144 . TLR activated by microbiota can cause derangements of multiple tumor suppressor proteins (e.g., p16, p21, p27, p53, pRb, PTEN, and MAP2K4), induce STAT3 activation, and enhance EMT and oncogene‐induced senescence 145 .…”
Section: Microbiota and Tumorigenesismentioning
confidence: 99%
“…Accumulating evidence suggests that microbiota play an important role in cancer by damaging cellular DNA, inducing transformation, activating and altering stromal cell components in the TME, and influencing cellular metabolism. 448,449 The microbiota characteristics under hypoxic conditions are currently not fully understood. Recent research has demonstrated that a combination of live bacteria and treatment modalities such as surgery, chemotherapy, and radiotherapy can produce good clinical outcomes.…”
Section: Biotherapymentioning
confidence: 99%
“…[ 138 ]. The aforementioned microbiota was reported to be strongly associated with the onset and progression of PC, which makes it possible as a biomarker for the noninvasive diagnosis of this disease [ 174 ].…”
Section: Pc and The Microbiomementioning
confidence: 99%